Physiotherapy as an immunoactive therapy? A pilot study - Rasova, Kamila; Dolezil, David; Kalistova, Hana; Kucera, Petr; Juzova, Olga; Zimova, Denisa; Medova, Eva; Jandova, Dobroslava; Tintera, Jaroslav; Ibrahim, Ibrahim; Zvara, Karel; Bicikova, Marie; et al. (Neuro endocrinology letters, 2012)
OBJECTIVES: The aim of this study was to confirm the immunoregulatory and anti-inflammatory changes in the immunologic profile after two months of the facilitation physiotherapy in patients with multiple sclerosis; and to determine whether the changes in the immunologic profile correlate with the changes in dehydroepiandrosterone, the brain microstructure and clinical functions. DESIGN & SETTING: A group of 12 patients with multiple sclerosis was examined twice: at the beginning and 2 months later after the patients had undergone the facilitation therapy. Standardized tests evaluating chosen clinical functions (balance, righting, equilibrium and protective reactions, tremor, dysdiadochokinesis, dysmetry, fine hand function and walking), immune parameters (parameters of the humoral and cellular immunity), dehydroepiandrosterone and diffusion tensor imaging (the fractional anisotropy, mean diffusivity) were measured. The patients underwent the facilitation physiotherapy in two sessions lasting two hours each week for two months. RESULTS: All clinical and diffusion tensor imaging parameters significantly improved following the therapy. Without the correction for multiple comparisons, there were significant changes in the IgG, IgG1 subclasses, in the numbers of Neutrophils and Lymphocytes, the T cells (CD3+) absolute number, the T cytotoxic subpopulation (CD3+CD8+) absolute number, B cells (CD19+) and the Natural killer cells. In addition, there was a significant correlation between the changes in the clinical functions and the changes in IgG1 (r=0.67), and between the changes in the mean diffusivity and the changes in CD3+CD8+ absolute (r=-0.61). The changes in the immune parameters and the mentioned correlations were not significant in view of the number of comparisons and thus necessitate further validation. No changes in the dehydroepiandrosterone concentration after the therapy were confirmed. CONCLUSION: The study suggests new possibilities of physiotherapy to influence the psycho-neuro-endocrine-immune response in patients with multiple sclerosis.
Keywords: techniky fyzikální terapie; pilotní projekty; Anisotropy; Physical Therapy Modalities; Pilot Projects; lidé; zobrazování difuzních tenzorů; Diffusion Tensor Imaging; roztroušená skleróza; anizotropie; Humans; Multiple Sclerosis